(untitled) - Ihnatko, Andy (Hoboken, N.J., 2005)
Introduces the Mac OS X Tiger operating system, covering installation, working with files and applications, network setups, using AppleScript, and computer security.
Keywords: Operating systems (Computers),Macintosh (Computer),Hệ điều hành (Máy tính),Macintosh (Máy tính); Programming,Lập trình máy tính